PENERAPAN FUNGSI-FUNGSI MANAJEMEN TERHADAP PENDAPATAN NELAYAN IKAN DI DESA LAGADING KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Monalisa Ibrahim; Marsita Marsita (Jurnal Bisnis dan Kewirausahaan, 2018)
This study aims to determine the application of Management Functions to Fishers Income in Lagading Village Pitu Riase District Sidenreng Rappang Regency and To determine the factors that affect the Application of Management Functions in Lagading Village Pitu Riase District Sidenreng Rappang District.The population in this study is the total number of fishermen in the village of Lagading is 106 people. Sample 51 people, taken by Simple Random Sampling technique. This type of research is descriptive quantitative. Data collection techniques are observation, interview, koesioner and literature study. Data analysis using likert scale. The results of this study indicate that the implementation of management functions are in the less good category that is 51% of fisherman's income is in good category that is 72%, while the factors that influence the implementation of management functions in Lagading Village Pitu Riase District Sidenreng Rappang Regency is 70 % are in either category.